Balance between cAMP and Ca2+ signals regulates expression levels of pituitary adenylate cyclase‐activating polypeptide gene in neurons. (7th July 2016) - Fukuchi, Mamoru; Kuwana, Yuki; Tabuchi, Akiko; Tsuda, Masaaki
Abstract : Mice lacking the gene encoding pituitary adenylate cyclase‐activating polypeptide (PACAP) or its specific receptor, PAC1, show abnormal behaviors related to schizophrenia. However, the regulation of PACAP expression in neurons remains unclear. Here, we report that Pacap mRNA levels are regulated transcriptionally and post‐transcriptionally by cAMP and Ca 2+ signals in cultured rat cortical cells. Pacap mRNA levels decreased proportionately with the intensity of cAMP signaling, and this decrease was accelerated by N‐methyl‐D‐aspartate (NMDA) receptor blockade, suggesting that cAMP signaling enhances the degradation of Pacap mRNA, whereas NMDA receptor‐mediated signals inhibit its degradation. However, depolarization (which produced a robust increase in Ca 2+ signals) together with cAMP signaling resulted in a synergistic induction of Pacap mRNA through calcineurin and its substrate, cAMP‐response element‐binding protein (CREB)‐regulated transcription coactivator 1. These results strongly support the concept that while cAMP signaling can accelerate the degradation of Pacap mRNA, it can also synergistically enhance Ca 2+ signaling‐induced transcriptional activation of Pacap . Taken together, our findings suggest that a balance between Ca 2+ and cAMP signals regulates PACAP levels in neurons and that a perturbation of this balance may result in psychiatric disorders, such as schizophrenia. Abstract : Ca 2+ signaling evoked by excitatory neurotransmission not only activates the Pacap promoter but also prevents Pacap mRNA degradation. In contrast, cAMP signals, which can be induced by Gs‐coupled GPCR activation, reduce the expression levels of Pacap mRNA. However, cAMP signals also participate in the synergistic induction of Pacap in the presence of Ca 2+ signals via calcineurin/CRTC1/CREB, resulting in robust PACAP expression in neurons.